Perturbation of Incenp function impedes anaphase chromatid movements and chromosomal passenger protein flux at centromeres - Ahonen, Leena J. (2008)
Incenp is an essential mitotic protein that, together with Aurora B, Survivin, and Borealin, forms the core of the chromosomal passenger protein complex (CPC). The CPC regulates various mitotic processes and functions to maintain genomic stability. The proper subcellular localization of the CPC and its full catalytic activity require the presence of each core subunit in the complex. We have investigated the mitotic tasks of the CPC using a function blocking antibody against Incenp microinjected into cells at different mitotic phases. This method allowed temporal analysis of CPC functions without perturbation of complex assembly or activity prior to injection. We have also studied the dynamic properties of Incenp and Aurora B using fusion protein photobleaching. We found that in early mitotic cells, Incenp and Aurora B exhibit dynamic turnover at centromeres, which is prevented by the anti-Incenp antibody. In these cells, the loss of centromeric CPC turnover is accompanied by forced mitotic exit without the execution of cytokinesis. Introduction of anti-Incenp antibody into early anaphase cells causes abnormalities in sister chromatid separation through defects in anaphase spindle functions. In summary, our data uncovers new mitotic roles for the CPC in anaphase and proposes that CPC turnover at centromeres modulates spindle assembly checkpoint signaling.